Fertilizer management practices for cassava in acid dryland of Sukabumi Regency, West Java - Sutrisno; Noerwijati, Kartika; Taufiq, Abdullah; Baliadi, Yuliantoro; Utomo, Joko Susilo; Yusnawan, Eriyanto; Amanah, Amri; Harnowo, Didik; Sundari, Titik; Koentjoro, Bambang Sri (Brawijaya University, 2024)
The productivity of cassava in acid dryland is generally still low. Fertilization, land amelioration, and superior varieties are the main solutions for increasing cassava productivity. This research aimed to determine the response of high-yielding varieties and fertilization technology packages to the growth and yield of cassava in acid dryland of Sukaharja Village, Warung Kiara District, Sukabumi Regency, West Java. The contents of organic carbon, nitrogen, and magnesium of the soil is below the minimum threshold, so the application of N fertilizer, organic matter, and ameliorant is expected to increase plant growth. The research consisted of two treatment factors: two cassava varieties and three fertilization technologies. The treatments were arranged in a completely randomized split-plot experimental design with three replications with variety as the main plot and fertilization technology package as the subplots. The treatment effect was observed on the character of plant height, wet biomass weight, stem diameter, number of tubers, tuber length, tuber diameter, tuber weight (large and small) per plant, and tuber yield per plot to be converted per ha. Tuber quality was observed by observing water content, percent dry matter, and starch yield. The results showed that the fertilization technology package increased plant height, fresh biomass weight, stem diameter, large tuber weight per plant, and yield per hectare in both varieties. Differences in varieties and fertilization technology packages have no effect on starch levels.